NARRATION AND DISCOURSE OF BHINNEKA TUNGGAL IKA IN INDONESIAN REVISED HISTORY TEXTBOOK: A HISTORY DIDACTICS APPROACH - Djono, Djono; Joebagio, Hermanu (History Department, Semarang State University and Historian Society of Indonesia, 2019)
The presented research depicts the narration and discourse of Bhinneka Tunggal Ika in the history subject. By using history didactic approach, this research focuses on two dimensions of analysis: (1) the narration and discourse of the history textbook and (2) teachersÃ¢â‚¬â„¢ interpretation as well as objectification towards the discourse of Bhinneka Tunggal Ika in the history textbook. The Socio-cognitive discourse analysis was used as the research method and attitude. The corpus of analysis was the revised edition of the compulsory history textbook published by The Republic of IndonesiaÃ¢â‚¬â„¢s Ministry of Education and Culture, and the research participants are 15 teachers of Senior High Schools in Surakarta. The remarkable finding of this research is the unequal position between unity and diversity. This research exposes that the textbook posits the narration and discourse of unity above the sense of diversity. These narrations and discourse are confirmed by the most of research participants in which they tend to articulate the importance of unity and integration in their interpretation. Following this interpretation, the teachersÃ¢â‚¬â„¢ objectification is postulated in some attitudes such as patriotic, mutual-cooperation, and solidarity, led to the ideology of nationalism. The authors highlighted the unequal position between unity and diversity as the crucial problem in the textbook narration and discourse that, in certain degrees, could become a latent problem for the national integration, such as minority intolerance and annihilation.Keywords: Bhinneka Tunggal Ika, history textbook, unity above diversityÃ‚Â Penelitian ini menggambarkan narasi dan wacana Bhinneka Tunggal Ika dalam mata pelajaran sejarah. Dengan menggunakan pendekatan didaktik sejarah, penelitian ini berfokus pada dua dimensi analisis: (1) narasi dan wacana buku teks sejarah dan (2) interpretasi guru serta objektifikasi terhadap wacana Bhinneka Tunggal Ika dalam buku teks sejarah. Analisis wacana sosial-kognitif digunakan sebagai metode dan sikap penelitian. Analisis teks menggunakan edisi revisi dari buku teks sejarah wajib yang diterbitkan oleh Kementerian Pendidikan dan Kebudayaan Republik Indonesia, dan peserta penelitian adalah 15 guru Sekolah Menengah Atas di Surakarta. Temuan dari penelitian ini adalah posisi yang tidak setara antara persatuan dan keanekaragaman. Penelitian ini mengungkap bahwa buku teks menempatkan narasi dan wacana persatuan di atas rasa keberagaman. Narasi dan wacana ini dikonfirmasi oleh sebagian besar peserta penelitian di mana mereka cenderung mengartikulasikan pentingnya persatuan dan integrasi dalam interpretasi mereka. Setelah interpretasi ini, objektifikasi guru dipostulatkan dalam beberapa sikap seperti patriotik, gotong royong, dan solidaritas, mengarah pada ideologi nasionalisme. Para penulis menyoroti posisi yang tidak setara antara persatuan dan keragaman sebagai masalah krusial dalam narasi dan wacana buku teks yang, dalam derajat tertentu, bisa menjadi masalah laten bagi integrasi nasional, seperti intoleransi minoritas dan pemusnahan.Kata kunci: Bhinneka Tunggal Ika, buku teks sejarah, kesatuan di atas keanekaragamanÃ‚Â